2003
DOI: 10.1002/adsc.200303104
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Enantioselective Hydrogenation of Activated Ketones Catalyzed by Modified Pt‐Catalysts: A Systematic Structure‐Selectivity Study

Abstract: A systematic structure-selectivity study was carried out for the enantioselective hydrogenation of activated ketones with chirally modified Pt/Al 2 O 3 catalysts. For this, 18 modifiers containing an extended aromatic system able to form a strong adsorption complex with the Pt surface, and a suitable chiral group with an amino function capable to interact with the keto group of the substrate (HCd, Qd, HCn, Qn, and semi-synthetic derivatives, as well as synthetic analogues) were prepared and tested on 8 differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 19 publications
(6 reference statements)
4
69
0
Order By: Relevance
“…[1][2][3][4] Thus, the synthesis of chiral compounds is of growing interest; among them, the hydrogenation of a-ketoesters and ketones is the most widely studied. [5][6][7][8][9][10][11][12][13][14][15] Since Orito et al reported the enantioselective hydrogenation of ethyl pyruvate to (R)-ethyl lactate over cinchonidine-modified Pt catalysts with ee's up to 95%, many other research teams have evaluated the performance of their catalytic systems in this reaction. [16][17][18] Indeed, this is nowadays a sort of test reaction in the field of asymmetric catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Thus, the synthesis of chiral compounds is of growing interest; among them, the hydrogenation of a-ketoesters and ketones is the most widely studied. [5][6][7][8][9][10][11][12][13][14][15] Since Orito et al reported the enantioselective hydrogenation of ethyl pyruvate to (R)-ethyl lactate over cinchonidine-modified Pt catalysts with ee's up to 95%, many other research teams have evaluated the performance of their catalytic systems in this reaction. [16][17][18] Indeed, this is nowadays a sort of test reaction in the field of asymmetric catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure was tested to find the optimal Literature data [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Oxidative cleavage [12][13][14][15] time for conversion of 1a or 2a to the isomers (Z/E)-3a or (Z/E)-4a. We monitored the ongoing conversion progress of substrates by taking micro-samples of the reaction mixture regularly, at 10-min intervals, which after extraction with diethyl ether in the presence of aqueous ammonia were analyzed by TLC (silica gel plates, methoxyethanol).…”
Section: Resultsmentioning
confidence: 99%
“…This paper described our work on influence of controlled microwave heating on activity of palladium solid supported (Pd/SS) catalysts in the heterogeneous isomerisation of four natural Cinchona alkaloids. We studied also possibility of analysis and isolation of the geometric isomers Z and E in Δ 3,10 -isomers, as they will be used as chiral ligands [7,8], catalysts and modifiers in asymmetric syntheses [9][10][11][12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[115,116] Particularly striking is the progress made in the chiral modification of supported Pt and Pd catalysts by means of cinchona alkaloids, applied in enantioselective hydrogenation of functionalized ketones and enantioselective hydrogenation of C=C bonds, respectively. [102,[117][118][119][120][121] In these cases, an important role is not only played by the conformation and adsorption modes of cinchona alkaloid on the metallic surface (orange sphere in Figure 7), but also by the polarity of the solvent used during the reaction (yellow sphere in Figure 7). [122] Figure 7 provides a three-dimensional view of two surface conformations of cinchonidine adsorbed on Pt surface.…”
Section: Modifications Of the Rh And Ir Hydrogenation Catalysts-mentioning
confidence: 99%